Servant leadership for hospitality sustainability: green psychological capital as a pathway to environmental citizenship behavior - Ahmed Hassan Abdou (Frontiers in Sustainability)
IntroductionThe hospitality industry is known for its intensive resource operations, making it a critical sector for promoting sustainability. This study empirically examines how environmentally specific servant leadership (ESSL) influences organizational citizenship behavior for the environment (OCBE) by fostering Green Psychological Capital (GPsyCap) as a psychological resource. Specifically, it investigates the direct impact of ESSL on GPsyCap and OCBE, as well as the mediating role of GPsyCap in the ESSL-OCBE relationship within the hospitality industry.MethodsData were collected using convenience sampling from 388 full-time employees working in eco-friendly five-star hotels in Egypt. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships between ESSL, GPsyCap, and OCBE.ResultsThe findings indicate that ESSL positively influences both GPsyCap and OCBE, demonstrating that environmentally responsible leadership fosters voluntary pro-environmental behaviors among employees. Furthermore, GPsyCap significantly predicts OCBE and partially mediates the relationship between ESSL and OCBE, suggesting that GPsyCap serves as a crucial psychological mechanism through which leadership practices are translated into employee-driven sustainability efforts.DiscussionBuilding on these empirical insights, the study contributes to theory by extending the Conservation of Resources (COR) Theory, Social Exchange Theory (SET), and the Stimulus-Organism-Response (SOR) Model, integrating green organizational (ESSL) and psychological (GPsyCap) resources within the hospitality sector. By positioning GPsyCap as a mediating construct, this study offers a novel perspective on how leadership-driven sustainability initiatives influence employees' pro-environmental behaviors. Practically, the study highlights the need for organizations to cultivate ESSL qualities in leaders, enhance GPsyCap among employees, and foster a culture of environmental stewardship to promote sustainability in the hospitality industry.